2010
DOI: 10.1146/annurev-bioeng-070909-105351
|View full text |Cite
|
Sign up to set email alerts
|

Topography, Cell Response, and Nerve Regeneration

Abstract: In the body, cells encounter a complex milieu of signals, including topographical cues. Imposed topography can affect cells on surfaces by promoting adhesion, spreading, alignment, morphological changes, and changes in gene expression. Neural response to topography is complex, and depends on the dimensions and shapes of physical features. Looking toward repair of nerve injuries, strategies are being explored to engineer guidance conduits with precise surface topographies. How neurons and other cell types sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
460
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(476 citation statements)
references
References 181 publications
(236 reference statements)
12
460
0
4
Order By: Relevance
“…1 Microenvironmental cues, such as cellular, biochemical, mechanical, and topographical cues, can influence cell behaviors, including viability, proliferation, differentiation, migration, and protein and gene expressions. [2][3][4][5][6] Notably, many native microenvironmental cues are lost in traditional twodimensional (2D) cultures, in which cells spread on substrates that are often several orders of magnitudes stiffer than brain tissue and lack the brain's extracellular matrix (ECM) organization. 7 Cells in 2D are forced to adapt a planar morphology and can form intercellular connections only in the lateral direction.…”
mentioning
confidence: 99%
“…1 Microenvironmental cues, such as cellular, biochemical, mechanical, and topographical cues, can influence cell behaviors, including viability, proliferation, differentiation, migration, and protein and gene expressions. [2][3][4][5][6] Notably, many native microenvironmental cues are lost in traditional twodimensional (2D) cultures, in which cells spread on substrates that are often several orders of magnitudes stiffer than brain tissue and lack the brain's extracellular matrix (ECM) organization. 7 Cells in 2D are forced to adapt a planar morphology and can form intercellular connections only in the lateral direction.…”
mentioning
confidence: 99%
“…This study showed that the introduction of an aligned matrix significantly increased Schwann cell migration and the rate of axonal growth after five days in culture [4]. Studies by Kim et al and later by Clements et al similarly allude to more efficient migration of Schwann cells and axonal regeneration through the addition of topographical guidance cues [18,21,41]. Similarly the introduction of structured fibres may have increased rates of migration and growth during the initial stages of repair.…”
Section: Discussionmentioning
confidence: 57%
“…Localised effects occur on the growth cone of the regenerating axons in response to contact mediated intraluminal guidance cues. The effects of this localised signalling on nerve repair are still being realised [21]. These localised changes in signalling result in overall changes in the axonal regenerative response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Among several different topographies, micrometer sized pillars have been used for different purposes such as to promote neuronal axonal growth and orientation [3][4][5] and cellular differentiation. [5][6][7][8] Smaller diameter pillars, nanopillars, are applied for different purposes, for example, examination of neuronal development 9 and pinning neurons.…”
Section: Introductionmentioning
confidence: 99%